Social workers’ role in the provision of services for families with children and youth with disabilities in Latvia, Slovakia, and Portugal - Rahim Rozina (SHS Web of Conferences, 2024)
The current qualitative case study aims at exploring the role of social workers in the provision of support services to families of children and youth with disabilities in Latvia, Slovakia, and Portugal. To get a deeper understanding of the knowledge and lived experiences of professionals, a qualitative research design was used. Using purposive sampling, fifteen participants were identified of which 11 were social workers and 4 other professions. Social workers work closely with other professions to support families of children and youth with disabilities. Even though most of the participants agreed to a face-to-face interview, there were a few who were not able to participate in person due to language and the nature of work; therefore, an online means of gathering the data was used for a few participants. A thematic analysis was used to identify themes in the study that explained the available support and social services to families, which come from both private and public institutions. The study also revealed community-based services (deinstitutionalization) process in these three European countries.